PENGARUH MEDIA PEMBELAJARAN REKA GEOMETRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V UPT SPF SD INPRES NIPA-NIPA KOTA MAKASSAR - Marsanda; Andi Dewi Riang Tati; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of REKA (Rebut Kartu) Geometry learning media on the mathematics learning outcomes of fifth-grade students at UPT SPF SD Inpres Nipa-Nipa, Makassar City. The background of this research stems from students' low understanding of geometric concepts and the limited use of engaging and interactive learning media. The research employed a quasi-experimental method using a Nonequivalent Control Group Design. The sample consisted of two classes: an experimental class (33 students) using REKA Geometry media, and a control class (31 students) using conventional methods. Data were collected through learning outcome tests (pretest and posttest), implementation observations, and documentation. The findings revealed that the implementation of REKA Geometry media was highly effective and significantly improved students' mathematics learning outcomes. The average posttest score of the experimental group was higher than that of the control group, and the Mann-Whitney U test showed a statistically significant difference between the two groups (p < 0.05). Therefore, REKA Geometry media proved to be effective in enhancing students’ understanding of two-dimensional shapes through a fun and collaborative game-based learning approach.